2020
DOI: 10.3390/en13020344
|View full text |Cite
|
Sign up to set email alerts
|

Hygrothermal Risk in Museum Buildings Located in Moderate Climate

Abstract: Works of art are sensitive to environmental factors—mainly temperature and relative humidity—which, when stable, are generally recommended as ideal protection conditions, but in historical museum buildings, the required conditions are difficult to maintain, due to a lack of adequate heating, ventilation and air-conditioning systems. The paper presents the analysis of one-year measurements of temperature and relative humidity in three different museums in Poland. The aim of the research was to identify the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…In some cases, even by the storing and preservation of historic artifacts in the museums can cause salt problems. [5][6] Because of the numerous factors, sometimes it can be a challenge to reveal the exact source of the appearing salt and moisture or to answer the question when and at what climatic conditions the salt damage occurs. For a more profound investigation of the background of these problems, we need to improve our toolsets used for monitoring historic buildings.…”
Section: Salt Problems In Historic Buildingsmentioning
confidence: 99%
“…In some cases, even by the storing and preservation of historic artifacts in the museums can cause salt problems. [5][6] Because of the numerous factors, sometimes it can be a challenge to reveal the exact source of the appearing salt and moisture or to answer the question when and at what climatic conditions the salt damage occurs. For a more profound investigation of the background of these problems, we need to improve our toolsets used for monitoring historic buildings.…”
Section: Salt Problems In Historic Buildingsmentioning
confidence: 99%
“…Indoors, the RH can significantly fluctuate. Even in such a well-controlled environments as museums, RH can fluctuate in relatively broad range: 10-80% [27]. It seems that the mould growth is almost impossible; however, as mentioned above, the main parameter is a w , which can be much higher due to surface condensation or accidental moistening.…”
Section: Introductionmentioning
confidence: 98%
“…Water is undoubtedly the most important factor for initiation of mould growth; however, temperature also has a major effect since biochemical processes are highly dependent on the metabolic activity of mould growth [1]. The recommendations for museums as well as the real temperature monitoring data have shown that the temperature fluctuations are usually between 10-30 • C [27][28][29] and almost never are below 5 • C or over 53 • C, which are the lower and upper limits for the fungal spore germination [30]. Therefore, for efficient mould growth prevention indoors, the critical factor is humidity, and temperature is only an accelerator.…”
Section: Introductionmentioning
confidence: 99%
“…Some museum buildings and rooms have poor thermal insulation and insufficient airtightness, leading to air leakage through gaps in windows or doors [4] or small thermal and/or moisture capacity of the wall materials. Others may use AC systems of insufficient capacity [5] or may lack human and financial resources to manage them. In museums located in historic buildings, architectural renovations and AC system upgrades for the sake of conservation may not be feasible [6] because of the preservation of their heritage value.…”
Section: Introductionmentioning
confidence: 99%